Quality of Life and Stress in Call Center Agents: A Study of the Mediation of the Five Facets of Mindfulness - Maia Monteiro, Raissa Ester; Tavares, Joel Jonathan Carvalho; Silva, Leonardo Júnior Souza; Luiz, Cynthia Borges; Meneses, Danilo Andrade de; Lopez, Luiz Carlos Serramo (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2025)
Call centers have become prominent in the service industry, characterized by factors triggering high employee stress. Regular mindfulness practice emerges as a strategy to promote mindfulness among workers, serving as an ally in mitigating psychological stress in the workplace context. The present study aimed to investigate the mediating role of the trait of mindfulness, including its facets, in the relationship between psychological quality of life and stress levels in call center operators. A total of 110 call center operators, aged between 19 and 51, participated in the study from a private company. The results revealed a significant indirect effect (b = -0.92 [95% BCa CI = -1.77; -0.19]), suggesting that the trait of mindfulness acts as a mediator in the relationship between psychological quality of life and stress. This finding implies that a propensity for mindfulness can play a protective role against stress. When investigating which specific facets of mindfulness exert a significant mediating effect, multiple mediation analysis indicated that the "non-judging" facet is the only trait mediating the relationship between psychological quality of life and stress. The results provide preliminary evidence highlighting the importance of mindfulness as a potential protective factor against psychological distress in the organizational environment.